2010
DOI: 10.1088/0004-6256/140/5/1241
|View full text |Cite
|
Sign up to set email alerts
|

MORE GALAXIES IN THE LOCAL VOLUME IMAGED IN Hα

Abstract: We have carried out an Hα flux measurement for 52 nearby galaxies as part of a general Hα imaging survey for the Local Volume sample of galaxies within 10 Mpc. Most of the objects are probable members of the groups around Maffei 2/IC 342, NGC 672/IC 1727, NGC 784, and the Orion galaxy. The measured Hα fluxes corrected for extinction are used to derive the galaxy star formation rate (SFR). We briefly discuss some basic scaling relations between SFR, hydrogen mass, and absolute magnitude of the Local Volume gala… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 84 publications
5
38
0
Order By: Relevance
“…Similar values were calculated at z ∼ 0 from the SDSS (Brinchmann et al 2004;Nakamura et al 2004) and SINGG (Hanish et al 2006) projects, and from local volume studies (James et al 2008;Karachentsev & Kaisin 2010). Several authors extended local studies to redshifts z < 0.3 using optical spectroscopy (Tresse & Maddox 1998;Sullivan et al 2000).…”
Section: Introductionsupporting
confidence: 65%
“…Similar values were calculated at z ∼ 0 from the SDSS (Brinchmann et al 2004;Nakamura et al 2004) and SINGG (Hanish et al 2006) projects, and from local volume studies (James et al 2008;Karachentsev & Kaisin 2010). Several authors extended local studies to redshifts z < 0.3 using optical spectroscopy (Tresse & Maddox 1998;Sullivan et al 2000).…”
Section: Introductionsupporting
confidence: 65%
“…Those cases are suspect, as such behaviour is not found in any of the other surveys. HE04 and Karachentsev & Kaisin (2010) show virtually no SFRs above 0.5 M ⊙ yr −1 , which can be attributed to the fact that their samples are mostly or totally composed of irregular galaxies with very low SFRs.…”
Section: Other Studiesmentioning
confidence: 97%
“…Finally, Karachentsev & Kaisin (2010) presented a study of 52 galaxies observed in Hα as part of a larger survey aimed to study a sample of galaxies in the Local Volume (207 galaxies within 10 Mpc). An important number of the galaxies observed belong to the Maffei 2/IC 342 complex.…”
Section: Ot H E R S T U D I E Smentioning
confidence: 99%
See 1 more Smart Citation
“…3-3 reproduced from Karachentsev and Kaisin (2010) who combined Hα observations from galaxies within 8 Mpc (in addition, the overplotted open square indicates typical values for the Milky Way). This can be seen in > Fig.…”
Section: Star Formation In the Local Galaxiesmentioning
confidence: 99%